Evaluating the association of preoperative parecoxib with acute pain trajectories after video-assisted thoracoscopic surgery: a single-centre cohort study in Taiwan - Hsiang-Ling Wu; Ying-Hsuan Tai; Mei-Yung Tsou; Kuang-Yi Chang; Yu-Hsiang Ling; Wei-Lun Fu (BMJ Open)
Objective The efficacy of parecoxib as pre-emptive analgesia still remains controversial. This study aimed to investigate how pre-emptive analgesia with parecoxib affected postoperative pain trajectories over time in patients undergoing thoracic surgery.Design Retrospective cohort study.Setting A single medical centre in Taiwan.Participants We collected 515 patients undergoing video-assisted thoracoscopic surgery at a tertiary medical centre between September 2016 and August 2017.Interventions Pre-emptive parecoxib before surgery.Primary and secondary outcome measures Daily numeric rating pain scores in the first postoperative week.Results A total of 196 (38.1%) of the recruited patients received parecoxib preoperatively. The latent curve analysis revealed that woman, higher body weight and postoperative use of parecoxib were associated with increased baseline level of pain scores over time (p=0.035, 0.005 and 0.048, respectively) but epidural analgesia and preoperative use of parecoxib were inclined to decrease it (both p<0.001). Regarding the decreasing trends of changes in daily pain scores, older age and epidural analgesia tended to steepen the slope (p=0.014 and <0.001, respectively). Preoperative use of parecoxib were also related to decreased frequency of rescue morphine medication (HR=0.4; 95% CI 0.25 to 0.65).Conclusions Pre-emptive analgesia with parecoxib was associated with decreased baseline pain scores but had no connection with pain decreasing trends over time. Latent curve analysis provided insights into the dynamic relationships among the analgesic modalities, patient characteristics and postoperative pain trajectories.